Disentangling seasonal from maternal effects on egg characteristics in western Baltic spring‐spawning herring Clupea harengus. Issue 6 (28th September 2022) - Huang, Amy T.; Alter, Katharina; Polte, Patrick; Peck, Myron A.
Abstract: In marine fishes, the timing of spawning determines the environment offspring will face and, therefore, the chances of early life stage survival. Different waves of Atlantic herring Clupea harengus spawn throughout spring in the western Baltic Sea, and the survival of offspring from early in the season has been low in the most recent decade. The authors assessed changes in egg traits from early, middle and late phases of the spawning season to examine whether seasonal and/or maternal effects influenced embryo survival. At each phase, fertilized eggs of six to eight females were incubated at two temperatures (7 and 13°C), and egg size, fertilization success, mortality and time to hatch were recorded. A compilation of data from 2017 to 2020 spawning seasons indicated that mean total length of females decreased with progression of the season and increasing in situ water temperature. For the sub‐set of females used in the laboratory study, early spawners were 7.6% larger and produced 14.2% larger eggs than late‐spring spawners. Fertilization success was consistently high (>90%), and mortality to hatch was low (<3%). Neither the former nor latter were influenced by season, but both were influenced by maternity. This significant female effect was, however, not related to any maternal trait measured here (total length, Fulton's condition factor or age). There was no maternal effect on development rate at 7 or 13°C. The results suggest that intrinsic differences among females or among spawning waves are unlikely to markedly contribute to the poor survival observed for progeny from early in the season in this population and point towards other extrinsic factors or processes acting on eggs or early larval stages ( e.g., seasonal match–mismatch dynamics with prey) as more likely causes of mortality.